SELF-EFFICACY AKADEMIK DAN PENYESUAIAN DIRI SISWA KELAS X SMA PATRA NUSA - Lidya, Siti Fatia; Darmayanti, Nefi (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
This research aims to empirically examine the relationship between academic self-efficacy withself adjustment on students. The subjects were students of class X Patra Nusa Senior HighSchool who totaled 67 students. The sampling technique used by the total sampling technique.Data collection was done using two scales, self adjustment and academic self-efficacy scale.Product moment correlation Analysis techniques was used to analysis the data. Based on theresults of data analysis, the correlation coefficient (rxy) of 0.613 with p <0.005 which meansthat there is a positive and significant relationship between academic self-efficacy with selfadjustmenton students in class X, which shows the higher the students academic self-efficacythe better their self adjustment ability. Conversely, the lower the students academic selfefficacy,the self adjustment ability is getting worse. Self academicefficacy gave 37.5% impact tostudentâsself adjustment of class X Patra Nusa Senior High School